MICROBIOLOGICAL ANALYSIS OF KUNUN-ZAKI: A FERMENTED MILLET DRINK IN BENIN CITY, EDO STATE, NIGERIA - Hilda Abiola Emmanuel-Akerele; Etin-Osa Edobor (University of Sultan Ageng Tirtayasa, 2021)
Microbiological and physicochemical analyses were carried out on samples of fermented millet drink Kunun Zaki. Fifteen samples were obtained from Ikpoba Hill Market and Aduwawa Quarters. The microbiological analysis was carried out using the standard plate count technique to determine the total microbial population. The mean count of bacteria and fungi was 2.57x107 cfu/ml and 0.98x107cfu/ml respectively. Microorganisms identified were Lactobacillus sp, Bacillius sp, Staphylococcus aureus, Streptococcus sp, Escherichia coli, Pseudomonas sp, Mucor sp and Fusarium sp. The mean value of the pH and titrable acidity was 4.26±0.09 and 2.73±0.08ml 0.1M NaOH respectively. The moisture content was high with a mean of 85.90±0.95 and mean solid content of 14.1±0.95. This study has shown that kunun-zaki sold in Ikpoba Hill Market and Aduwawa Quarters is highly contaminated with microorganisms. Practices of good hygiene are therefore necessary in an environment where kunun-zaki is produced, stored, prepared and packaged.